Alcohol, smoking, recreational drug use and association with virological outcomes among people living with HIV: cross‐sectional and longitudinal analyses. Issue 3 (11th October 2021) - Jones, Timothy P. W.; Lampe, Fiona C.; Arenas‐Pinto, Alejandro; Smith, Colette; McDonnell, Jeff; Haddow, Lewis; Johnson, Margaret; Yousef, Elaney; Lascar, Monica; Maria Geretti, Anna; Sherr, Lorraine; Collins, Simon; et al.
Abstract: Objectives: There is increasing evidence to suggest that people living with HIV (PLWH) have significant morbidity from alcohol, recreational drug use and cigarette smoking. Our aim was to report associations of these factors with antiretroviral therapy (ART) non‐adherence, viral non‐suppression and subsequent viral rebound in PLWH. Methods: The Antiretroviral Sexual Transmission Risk and Attitudes (ASTRA) study recruited PLWH attending eight outpatient clinics in England between February 2011 and December 2012. Data included self‐reported excessive drinking (estimated consumption of > 20 units of alcohol/week), alcohol dependency (CAGE score ≥ 2 with current alcohol consumption), recreational drug use (including injection drug use in the past 3 months), and smoking status. Among participants established on ART, cross‐sectional associations with ART non‐adherence [missing ≥2 consecutive days of ART on ≥2 occasions in the past three months] and viral‐non suppression [viral load (VL) > 50 copies/mL] were assessed using logistic regression. In participants from one centre, longitudinal associations with subsequent viral rebound (first VL > 200 copies/mL) in those on ART with VL ≤ 50 copies/mL at baseline were assessed using Cox regression during a 7‐year follow‐up. Results: Among 3258 PLWH, 2248 (69.0%) were men who have sex with men, 373 (11.4%) were heterosexual men, and 637 (19.6%) were women. A CAGE score ≥ 2 was found in 568 (17.6%) participants, 325 (10.1%) drank > 20 units/week, 1011 (31.5%) currently smoked, 1242 (38.1%) used recreational drugs and 74 (2.3%) reported injection drug use. In each case, prevalence was much more common among men than among women. Among 2459 people on ART who started at least 6 months previously, a CAGE score ≥ 2, drinking > 20 units per week, current smoking, injection and non‐injection drug use were all associated with ART non‐adherence. After adjusting for demographic and socioeconomic factors, CAGE score ≥ 2 [adjusted odds ratio (aOR) = 1.52, 95% confidence interval (CI): 1.09–2.13], current smoking (aOR = 1.58, 95% CI: 1.10–2.17) and injection drug use (aOR = 2.11, 95% CI: 1.00–4.47) were associated with viral non‐suppression. During follow‐up of a subset of 592 people virally suppressed at recruitment, a CAGE score ≥ 2 [adjusted hazard ratio (aHR) = 1.66, 95% CI: 1.03–2.74], use of 3 or more non‐injection drugs (aHR = 1.82, 95% CI: 1.12–3.57) and injection drug use (aHR = 2.73, 95% CI: 1.08–6.89) were associated with viral rebound. Conclusions: Screening and treatment for alcohol, cigarette and drug use should be integrated into HIV outpatient clinics, while clinicians should be alert to the potential for poorer virological outcomes.